Pengaruh Model Pembelajaran Pemecahan Masalah (Pbl) Yang Di Tinjau Dari Minat Belajar Peserta Didik Dalam Belajar Senam Dasar - Febrian, Rizky; Rahayu, Ega Trisna; Suherman, Asep (Peneliti.net, 2023)
Educators serve as the spearhead of curriculum development and as implementers of the curriculum in the field, which is a key factor in the success of the curriculum. According to researchers preblem based learning model (PBL) is a method triggered by problems that encourage students to learn and work cooperatively in groups to get solutions, think critically and analytically, be able to determine and use appropriate learning resources. Physical education is an important part of the overall education system, so it must be directed towards achieving educational goals. To achieve these goals, specialist sports teachers and classroom teachers must work together (Lynch, 2015).One method of collecting data is by using the test method. The test method is used to determine the number of scores obtained by students after the pretest and posttest using Kiorroga Activities. The test was carried out in two stages, namely the pretest and posttest stages. In the pretest stage the results are used to determine the development of children's fine motor skills before being given treatment and for the posttest the results are used to see the extent of the development of fine motor skills of students after practicing basic gymnastic activities such as (front roll, back). The population of this study consisted of 16 students of class VIIl at AZZHAHIRIYYAH Islamic Junior High School located on the Karawang-Bekasi border. The pre-experimental method was used in this research, with a one group pretest-postest design. Saying that Pre-experimental design is a design that includes only one group or class that is given a pre and post test. This one group pretest and posttest design, carried out on one group without a control or comparison group (Sugiyono, 2014: 109). This research instrument is in the form of multiple choice with 30 questions and one answer score. The Likert scale was used to calculate the score in this review. The Likert scale according to Sugyono (2018) is used to assess the perceptions, beliefs, and attitudes of a person or group towards social phenomena. Several stages or steps that must be considered in the preparation of instruments include construct planning, factor evaluation, indicator preparation, and question item preparation (Irfan Zinat Achmad, 2017). The statistical tests used are N-gain scores, Kolmogorov-Smirnov normality test, homogeneity test with Levene statistics, and paired sample test. This research resulted in the finding that the problem-based learning model (PBL) has a significant effect on the child's motor skills in performing basic gymnastic movements. After we know the data from the three tests, the problem-based learning model (problem-solving learning model) provides many benefits for students, Bruner in Dahar (2011) considers that